A simple and large-scale method to prepare flexible hollow graphene fibers for a high-performance all-solid fiber supercapacitor. (15th September 2017) - Jiang, Degang; Zhang, Jizhen; Li, Chenwei; Yang, Wenrong; Liu, Jingquan
Abstract : The fabrication of hollow graphene fibers (HGFs) via simple spray deposition of GO on silk fiber templates for a flexible supercapacitor. Abstract : Herein, we develop a spray deposition process for the production of flexible and conductive hollow graphene fibers (HGFs). Firstly, a graphene oxide suspension is spray-coated on silk fibers, which act as a template, followed by the reduction of GO into RGO using HI as the reductant. This simple method gets rid of the picky conditions and complicated process for the fabrication of graphene fibers (GFs) which possess good flexibility, conductivity and a hollow structure. A flexible all-solid hollow graphene fiber supercapacitor (HGFS) is assembled using the as-prepared HGFs and shows an excellent specific capacitance of 76.1 F g −1 (127.4 mF cm −2, 48.5 F cm −3 ) at a current density of 1 A g −1, excellent rate capability (over 87% retention at 5 A g −1 ) and high cycling stability with only 9.5% capacitance decay over 2000 recycles at a scan rate of 100 mV s −1 . This simple large-scale template method for the preparation of flexible and conductive HGF electrodes could promise broad prospects for high-performance energy storage applications, particularly for next-generation wearable electronic devices.